2015
DOI: 10.1021/am507421y
|View full text |Cite
|
Sign up to set email alerts
|

Facile Conversion of Commercial Coarse-Type LiCoO2 to Nanocomposite-Separated Nanolayer Architectures as a Way for Electrode Performance Enhancement

Abstract: Coarse-type LiCoO2 is the state-of-the-art cathode material in small-scale lithium-ion batteries (LIBs); however, poor rate performance and cycling stability limit its large-scale applications. Here we report the modification of coarse-type LiCoO2 (LCO) with nanosized lithium lanthanum titanate (Li3xLa2/3-xTiO3, LLTO) through a facile sol-gel process, the electrochemical performance of commercial LiCoO2 is improved effectively, in particular at high rates. The crystalline structure of pristine LiCoO2 is not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This well-known structure consists of alternating planes of coordinated Li and Co ions, which are separated by close-packed oxygen layers. 48,49 According to Rietveld renement of the XRD data, the lattice parameters were found to be a ¼ b ¼ 2.817(6)Å and c ¼ 14.05 (8) A (c/a ¼ 4.988), which were in alignment with the literature results, [48][49][50] and further suggested a well-formed layered structure of LiCoO 2 . The XRD of commercial Pt/C presents broad diffraction peaks, indicating the nanoscale crystalline characteristic of the Pt particles.…”
Section: Resultssupporting
confidence: 87%
“…This well-known structure consists of alternating planes of coordinated Li and Co ions, which are separated by close-packed oxygen layers. 48,49 According to Rietveld renement of the XRD data, the lattice parameters were found to be a ¼ b ¼ 2.817(6)Å and c ¼ 14.05 (8) A (c/a ¼ 4.988), which were in alignment with the literature results, [48][49][50] and further suggested a well-formed layered structure of LiCoO 2 . The XRD of commercial Pt/C presents broad diffraction peaks, indicating the nanoscale crystalline characteristic of the Pt particles.…”
Section: Resultssupporting
confidence: 87%
“…The results obtained are consistent with the theoretical predictions described by Han et al [42], where the strength and resilience of the peptides were found to be greatly enhanced through their interaction with graphene. Accordingly, one can suppose that the rGO/Ni layer tends to participate in the peptide intramolecular interactions and integrates into the interchain of β-sheets in protein domains thus enhancing the stability of PMT/rGO/Ni structure [43].…”
Section: Resultsmentioning
confidence: 99%
“…Since the first commercialization of LIB in 1991, LCO and layered‐structured Co‐rich materials have been still frequently utilized as cathode materials for LIBs, especially for portable IT devices (e.g., smartphone, electric vehicles, and laptop), thanks to their high volumetric energy density. [ 22,23,32,74,102–110 ] Volumetric energy density of active materials of LIB is determined with three terms: discharge capacity, working voltage, and electrode density, as shown in the equation below. leftVolumetric energy densityElectrode=Discharge capacity × Working voltage×Electrode density …”
Section: Recent Research: Electrochemical Reaction Mechanism Control Dopingmentioning
confidence: 99%